HIV Interactions with Dendritic Cells Infection and Immunity - Wu, Li.; Schwartz, Olivier. (Advances in Experimental Medicine and Biology,, 2013)
Given rapid research progress and advance of the techniques in studying HIV interactions with host cells and factors, there is a critical need for a book on HIV interactions with DCs. The proposed book will aim for a broad readership to facilitate HIV/AIDS research and provide a practical tool for HIV researchers to continuously address novel questions. Specifically, the editors will summarize the literature in this field and provide critical analysis and future directions. International researchers will be invited as contributors of the book, highlighting authors who have contributed significantly to the field from different angles and aspects of virology, cell biology and immunology, etc.